Polish physicians' views on compounded medicines and factors related to the frequency of their prescription - Piotr Guzy; Andrzej Porębski; Sławomir Łudzik; Natalia Obajtek; Anna Gołda (Polskie Towarzystwo Farmaceutyczne, 2024)
The aim of this study was to verify if there is a relationship between physicians' specialization, place of practice, or views on issues related to compounded medicines and the frequency of prescribing such formulations. Additionally, the study aimed to determine the factors that influence these views. The study also examined the barriers and encouragements, according to physicians, in the use of compounded medicines. The original questionnaire was developed specifically for this study. Included sample consisted of Polish-speaking physicians whose main specialization was gynaecology, gastroenterology, dermatology, family medicine, internal medicine, otorhinolaryngology, paediatric otorhinolaryngology, paediatrics. Answers were gathered using computer-assisted telephone interview. The majority of surveyed physicians believed that every Polish patient receives treatment tailored to their personal needs (68,7%) and agreed that compounded medicines are a way to facilitate individualization of pharmacotherapy (79,3%). Frequency of prescribing of magistral formulations, as well as views on quality of compounded medicines, ease of prescribing, and filling a prescription vary between specializations and places of practice. The problem that negatively affects the practice of the largest group of respondents was complicated and frequently changing legal regulations (63.3%), while the least frequently indicated problems were concerns about the quality of preparation (16.7%). Based on opinion of surveyed physicians, a simplification of the regulations for prescribing and liberalization of reimbursement rules are main changes to consider in order to improve clinical practice in the areas where it relates to the prescription of compounded medicines.